Students’ interest in learning mathematical literacy: What is its role in the mathematical economics course? - Maria Edistianda Eka Saputri (Universitas Jambi, Indonesia, 2025)
This research examines the role of learning interest in students' mathematical literacy in the mathematical economics course. This research was carried out at a private college. The instruments included questionnaires and tests. The data analysis techniques used were the Pearson correlation, regression, and ANOVA tests. The research results show that interest in learning significantly affects students' mathematical literacy in the mathematical economics course. Apart from that, there is a significant difference in the average value of mathematical literacy between students in the low, moderate, and high learning interest categories. Students with a low interest in learning have significant differences in mathematical literacy from students with a high interest in learning. Students with a moderate interest in learning have significant differences in mathematical literacy from students with a high interest in learning. Meanwhile, students with low interest in learning do not significantly differ in mathematical literacy from those with moderate interest in learning.